The Influence of Influencer Collaboration, Augmented Reality Marketing, and Personalized Recommendations on Consumer Purchasing Decisions in the Beauty Industry in Indonesia - Sudirjo, Frans; Sumerli A., Chevy Herli; Souisa, Wendy; Vandika, Arnes Yuli (Westscience Press, 2024)
This study investigates the influence of influencer collaboration, augmented reality marketing, and personalized recommendations on consumer purchasing decisions in the beauty industry in Indonesia. A quantitative analysis was conducted based on survey data collected from 170 Indonesian consumers. The findings reveal significant positive relationships between influencer collaboration, augmented reality marketing, personalized recommendations, and consumer purchasing decisions. Influencer collaboration, augmented reality marketing, and personalized recommendations emerged as critical drivers of consumer behavior, highlighting the importance of digital marketing strategies in shaping purchase intentions and driving sales in the competitive beauty market. These findings offer valuable insights for marketers and businesses seeking to optimize their marketing strategies and enhance consumer engagement in the Indonesian beauty industry.